Classroom Discourse Analysis on English Learning Interaction During the Covid-19 Pandemic - Nur Azizah; Dwijani Ratnadewi; Sofi Yunianti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
AbstractThe spread of Covid-19 has an impact on changing learning patterns from offline learning to online learning or hybrid types. This phenomenon intends to fill the gap that this research analyzes both offline and online learning during pandemic Covid19. The learning pattern was investigated to obtain information about the characteristics of the learning pattern, advantages, disadvantages, and benefits in classroom interaction. The aims of this study are to find out the types of teacherstudent interaction patterns in the classroom (IRF patterns) in offline and online learning, to describe the IRF patterns in each learning interaction, and to identify IRF patterns that frequently appear. The participants in this study were 18 mathematics and science class students from a private high school in Surabaya, Indonesia. The main data were teacher-students interaction in the English class, collected by observing and recording the class offline and online learning and they were analyzed by applying the IRF theory of Sinclair and Coulthard. The results of data analysis showed that there were eleven kinds of exchanges in offline and online learning. In offline learning the initiation-response-feedback (IRF) pattern was balanced between the teacher and the students, while in online learning, the teacher was more dominant in providing explanations and initiations, while students were less active. Therefore, this study implicates on how to implement appropriate communication in teaching learning process.